Hydrocarbon Reservoir Characterization Using Well Logs of Nahr Umr Formation in Kifl Oil field, Central Iraq - AL-Baldawi, Buraq Adnan (Iraqi Journal of Science, 2022)
This study aims to determine the petrophysical characteristics of the three wells in the Kifl Oilfield, central Iraq. The well logs were used to characterize hydrocarbon reservoirs to assess the hydrocarbon prospectivity, designate hydrocarbon and water-bearing zones, and determine the Nahr Umr Formation’s petrophysical parameters. The Nahr Umr reservoir mainly consists of sandstone at the bottom and has an upper shale zone containing a small proportion of oil. The geophysical logs data from three oil wells include gamma-ray, resistivity, neutron, density, acoustic, and spontaneous potential logs. A gamma-ray log was employed for lithology differentiation, and a resistivity log was used to determine the response of distinct zones’ productivity. The petrophysical parameters of shale volume, total porosity, effective porosity, water saturation, hydrocarbon saturation, and flushed zone saturation were evaluated using computer processing analyses (CPI). These parameters were plotted by interactive petrophysics (IP) software. The effective porosity (PHE) in the sandstone unit ranges between 3.2 and 31.2%, water saturation (SW) ranges between 6.6 and 100%, and hydrocarbon saturation and (Sh) range from 6 to 65%. The Nahr Umr Formation has moderate to low reservoir characteristics in the lower sandstone unit.